TEKNIK DAN GAYA TARI MANDUDA PADA MASYARAKAT SIMALUNGUN ATAS DAN MASYARAKAT SIMALUNGUN BAWAH - Nurul Aprila Putri Aprilia Putri (Universitas Negeri Medan, 2013)
This study uses the theories that relate to topics such as the theory of style,sense Habonaron Do Bona,dance technique and dance MandudA.Time understanding of research conducted for 3 months in June 2013 to August 2013.Locationi Simelungun research conducted in the Upper Subdistrict Sidamanik whereas in Simelungun Under the Airport District.The method used is descriptive qualitative method,the population in this study as well as a sample of speakers,dancers,cultural figures and artists who know the techniques and styles of dance in society Simelungun Manduda Up and Bottom.Techniques library study includes data collection,observation interviews and documentation.Based on the research conducted,it is described that the technique is basically the same Manduda dance,both in Simelungun Upper and Lower.There are four dominant motion technique on the dance Manduda ondok,herbang,manerser and eot.Manduda dance there are 15 wide,wide differences in dance movements Manduda Simelungun Upper and Lower Simelungun ie the range to 10.Geographical location affect differences in dance styles of dance Manduda. Do Habonaron values ​​Bona on Manduda dance in public Simelungun Upper and Lower are the same people.